2007
DOI: 10.1016/j.ijgo.2007.03.038
|View full text |Cite
|
Sign up to set email alerts
|

Maternal iron status and neonatal outcomes in women with pica during pregnancy

Abstract: Pica (from the Latin pica, a magpie), or the compulsive intake of nonnutritive substances, has been associated with iron deficiency during pregnancy [1][2][3][4]. This study was conducted at a hospital in suburban Buenos Aires, Argentina, to determine whether there were differences in iron concentration between women with pica and controls during the postpartum period. Biochemical indicators of iron status and anthropometric characteristics of neonates were compared.After calculating sample size needed to esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
1
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 3 publications
2
9
1
2
Order By: Relevance
“…In another study performed on 15 lambs having pica symptoms; iron deficiency was found and it was related to the aetiology of pica in lambs (Aytekin et al 2010). Similar findings were also reported for human beings (Lopez et al 2007). Furthermore, Nikvand et al (2018) reported that low serum iron concentrations appear to prompt chronic nutritional iron inadequacy, which increase the risk of pica in cattle due to iron deficiency.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In another study performed on 15 lambs having pica symptoms; iron deficiency was found and it was related to the aetiology of pica in lambs (Aytekin et al 2010). Similar findings were also reported for human beings (Lopez et al 2007). Furthermore, Nikvand et al (2018) reported that low serum iron concentrations appear to prompt chronic nutritional iron inadequacy, which increase the risk of pica in cattle due to iron deficiency.…”
Section: Discussionsupporting
confidence: 90%
“…In contrast to our results, Naci et al (2008) investigated 30 cattle that suffered from pica and had normal amounts of calcium, copper and zinc but slightly elevated iron concentration. Although many researches (Lopez et al 2007;Aytekin et al 2010;Nikvand et al 2018) with regard to low serum iron value in animals with pica are in agreement with the present study, some papers (Akg€ ul et al 2000;Naci et al 2008) do not agree with each other or with us about the role of the other elements, especially iron and copper, in the occurrence of pica. To determine the main causes of pica, several studies were carried out on cattle, horses and lambs.…”
Section: Discussionsupporting
confidence: 76%
“…Estudo recente em 71 gestantes argentinas apontou as manifestações mais comuns de pica: 70% de gelo, 18% de terra, 4% de sabão, 3% de giz e 4% de linha, esmalte e sal. O artigo ainda ressalta a periodicidade diária do comportamento, além do fato de que a prevalência de anemia ferropriva no grupo estudado (30%) foi muito maior do que aquela encontrada no grupo-controle (14%) 4 . Em estudo realizado no Quênia, foi encontrada prevalência de 45,7% de geofagia, que diminuía para 34% e 29% após 3 e 6 meses de puerpério, respectivamente 30 .…”
Section: Aspectos Psiquiátricosunclassified
“…Walker et al 2 expandem o conceito, descrevendo a pica não apenas como um transtorno manifestado pela ingestão inusual de determinadas substâncias, mas também que ocorre em grandes quantidades. Outros autores ainda falam em ingestão compulsiva de alimentos não nutritivos 3,4 . Ao longo da história, o comportamento de pica tem sido um enigma fascinante para seus estudiosos, uma vez que não existe consenso a respeito de sua etiologia, invocando fatores sociais, culturais, psicológicos, biológicos e comportamentais, embora, sem dúvida nenhuma, possua um componente ambiental importante 5 .…”
Section: Introductionunclassified
“…It occurs most commonly in pregnant women (Vermeer and Ferrell 1985;Rainville 1997;Kikouama et al 2007Kikouama et al , 2009López et al 2007). There are several explanations for this use of clays.…”
Section: Introductionmentioning
confidence: 99%